Incorporating fantasy into gamification promotes student learning and quality of online interaction - Bai, Shurui; Hew, Khe Foon; Gonda, Donn Emmanuel; Huang, Biyun; Liang, Xinyi (International Journal of Educational Technology in Higher Education, 2022)
We used the design-based research approach to test and refine a theoretically grounded goal-access-feedback-challenge-collaboration gamification model. The testbed was a 10-week, university-level e-learning design course offered in two consecutive semesters. In Study 1, we implemented the initial goal-access-feedback-challenge-collaboration model in semester one of the 2020–2021 academic year ( N = 26). The aim was to enhance student behavioral engagement in online discussion forums, affective engagement in the class, and learning performance. The results of Study 1 showed that although most participants were engaged in this gamified learning experience during the first two sessions, they gradually lost interest and their participation in online discussions dropped over the next eight weeks. Thus, we introduced a new element, fantasy , into the original model. In Study 2, we tested the effectiveness of the goal-access-feedback-challenge-collaboration-fantasy model on students’ learning outcomes in semester two of 2020–2021 ( N = 23). The results of Study 2 suggested that, compared to the original model, the goal-access-feedback-challenge-collaboration-fantasy model can better promote students’ engagement in online discussion, as measured by increased interaction with peers, learning experience, and learning performance.